Foundations in Germany: a portrait - Anheier, Helmut K.; Förster, Sarah; Mangold, Janina; Striebing, Clemens (American behavioral scientist, 2018)
The article presents the findings of a research project on the roles and positioning of foundations in Germany, with a focus on the fields of education, higher ...
Gesehen am 27.05.2020